Evaluation of facility and community-based active household tuberculosis contact investigation in Ethiopia: a cross-sectional study - Fana Tefera; Gena Barnabee; Anjali Sharma; Beniam Feleke; Daniel Atnafu; Negasi Haymanot; Gabrielle O'Malley; Getachew Feleke (BMC, 2019)
Abstract Background No established strategy for household tuberculosis (TB) contact investigation (HTCI) exists in Ethiopia. We implemented integrated, active HTCI model into two hospitals and surrounding community health services to determine yield of active HTCI of all forms of TB and explore factors associated with active TB diagnosis in household contacts (HHCs). Methods Case managers obtained HHC information from index cases at TB/DOTS clinic and liaised with health extension workers (HEWs) who screened HHCs for TB at household and referred contacts under five and presumptive cases for diagnostic investigation. Results From 363 all forms TB index cases, 1509 (99%) HHCs were screened and 809 (54%) referred, yielding 19 (1.3%) all forms TB cases. HTCI of sputum smear-positive pulmonary TB (SS + PTB) index cases produced yield of 4.3%. HHCs with active TB were more likely to be malnourished (OR: 3.39, 95%CI: 1.19-9.64), live in households with SS + PTB index case (OR: 7.43, 95%CI: 1.64-33.73) or TB history (OR: 4.18, 95%CI: 1.51-11.55). Conclusion Active HTCI of all forms of TB cases produced comparable or higher yield than reported elsewhere. HTCI contributes to improved and timely case detection of Tuberculosis among population who may not seek health care due to minimal symptoms or access issues. Active HTCI can successfully be implemented through integrated approach with existing community TB programs for better coordination and efficiency. Referral criteria should include factors significantly associated with active disease.